Collaborative Governance for Inclusive Education: LKIS and The Struggle for The Right to Education for Believers of Indigenous Faiths in Yogyakarta - Ramadhani, Farah; Amaliah, Nurul (Unnes Political Science Journal, 2024)
Education is a fundamental right possessed by every citizen. As a rule-of-law state, Indonesia has established various regulations regarding education to ensure it runs smoothly and inclusively. However, the reality on the ground often contradicts what most people envision today. Many citizens still do not have access to their educational rights, particularly in the case of religious and belief education experienced by students from belief communities in Yogyakarta. LKIS, as one of the NGOs in Yogyakarta, plays a central role in advocating for this issue. This research will further explore a collaborative movement carried out by LKIS, the government, and other community and state institutions. The study employs a qualitative research method with a case study approach. The findings of the research show that, in its struggle, LKIS adopts both top-down and bottom-up approaches, which later form the foundation for cross-sector collaboration. This collaboration marks the beginning of a movement, driven by LKIS and other NGOs, to address and support issues and actions for the belief community.